Pembuatan Lift Barang Untuk Rumah Dua Lantai - Totok Suwanda; Sudarisman, Sudarisman; Ajis Kurniawan; Nur Ardiyansyah (Yayasan Literasi Sains Indonesia, 2023)
Limited land availability is a major obstacle to occupancy in Indonesia. In addition, residential owners who have constraints on physical limitations will have difficulty going up and down stairs by carrying loads. Based on these problems, the manufacture of a goods elevator with a carried out for a two-story house. The process of making a goods elevator starts from the process of re-design, preparation of materials tools and manufacturing process. Manufacturing processes in the manufacture of elevators include cutting, welding and pouring processes. Furthermore, the manufacturing process is divided into three parts, namely the manufacture of the main frame, the manufacture of cages and the place of electrical hoist as a drive pulley. The results of the elevator have dimensions of 6 meters in length of 0.8 meters and a width of 0.8 meters, while the cage has a height dimension of 1.5 meters long 0.74 meters and a width of 0.74 meters. The main frame construction uses the UNP 65×40×4 profile and the L 40×40×2 profile which is connected through part of the SMAW welding process and bolt nut connection. While in the cage using hollow profile baja 30×30×2, UNP 65×35×4 and wire mesh wire. Tempat electrical hoist uses UNP 85×45×5 profile and L 70×70×5 profile. The drive system in the elevator uses a 1200 kg PA electrical hoist with a single-phase 1800 watt electric power specification with a voltage of 220 V.